Composite non-stick layer, preparation method of composite non-stick layer, cookware and cooking utensil

By applying a composite non-stick layer on the pot and using a combined structure of a hard skeleton and non-stick filler, the problem of insufficient wear resistance and non-stickness of the traditional non-stick pan coating is solved, and better wear resistance and non-stickness are achieved, and the service life of the pot is extended.

CN119856867AActive Publication Date: 2025-04-22GUANGDONG MIDEA CONSUMER ELECTRICS MFG CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311359584.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The traditional non-stick coating has poor wear resistance, is not resistant to metal spatulas and steel wisps, and is insufficient non-stick, which cannot meet market expectations.

Method used

A composite non-stick layer structure is adopted, including a substrate layer and a non-stick coating. The non-stick coating consists of a first hard frame and a non-stick filler. The first hard frame has a through pore with a porosity of 5%-30%, and the non-stick filler is filled in the pores.

Benefits of technology

It achieves good wear resistance and non-stickness of the composite non-stick layer, extends the service life of the pot and improves the cooking experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856867A_ABST
    Figure CN119856867A_ABST
Patent Text Reader

Abstract

The invention provides a composite non-stick layer, a preparation method of the composite non-stick layer, a pot and a cooking utensil. The composite non-stick layer comprises: a substrate layer having a first surface; the non-stick coating is arranged on the first surface, the non-stick coating comprises a first coating, the first coating comprises a first hard framework and a non-stick filler, the first hard framework is provided with through pores, the pores are filled with the non-stick filler, and the porosity of the first hard framework is 5%-30%. The first hard framework in the first coating can provide better wear resistance for the non-stick coating, and the non-stick filler filled in the pores can provide good non-stick property for the non-stick coating, so that the composite non-stick layer disclosed by the invention has good wear resistance and non-stick property at the same time. Wherein the porosity of the first hard framework is 5%-30%, so that the proportion of pores is proper, the filling of the non-stick filler can be effectively met, and the composite non-stick layer has good non-stick property and also has good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of household electrical appliances, and in particular to a composite non-stick layer and a preparation method thereof, a pot and a cooking utensil. Background Art

[0002] As people's demand for easy-to-clean cooking utensils continues to increase, it is more common for frying pans to use non-stick coatings. However, traditional coated non-stick pans have low hardness, poor wear resistance, and are not resistant to metal spatulas and steel wool. Traditional metal pots, such as stainless steel pots and iron pots, can be cooked with metal spatulas and cleaned with steel wool, but they have poor non-stick properties and a poor cooking experience. In order to solve the problems of short life, non-wear resistance, and easy shedding of non-stick coatings, the industry began to study the lotus leaf effect, engraving concave and convex micro-nano structures on the surface of the pot body to achieve wear-resistant and non-stick effects. However, this physical non-stick layer uses more concave and convex structures to lock in oil, requiring users to actively add oil when cooking and form an oil film on the surface of the pot body after heating to achieve a certain degree of non-stickiness. This is not a true non-stick pan. The actual non-stick effect will change with the length of use or the amount of oil added, and cannot meet market expectations. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a composite non-stick layer, which has better wear resistance and non-stick properties.

[0004] In one aspect of the present invention, the present invention provides a composite non-stick layer. According to an embodiment of the present invention, the composite non-stick layer includes: a substrate layer, the substrate layer has a first surface; a non-stick coating, the non-stick coating is arranged on the first surface, the non-stick coating includes a first coating, the first coating includes a first hard skeleton and a non-stick filler, the first hard skeleton has through pores, the non-stick filler is filled in the pores, wherein the porosity of the first hard skeleton is 5%-30%. Thus, the first hard skeleton in the first coating can provide better wear resistance for the non-stick coating, and the non-stick filler filled in the pores can provide good non-stick properties for the non-stick coating, that is, the composite non-stick layer of the present invention has good wear resistance and non-stick properties at the same time. Among them, the porosity of the first hard skeleton is 5%-30%. In this way, the proportion of pores is appropriate, which can effectively meet the filling of non-stick fillers, so that the composite non-stick layer has good non-stick properties and good wear resistance at the same time; if the porosity is less than 5%, the proportion of the non-stick surface area of ​​the non-stick coating is too low, and the non-stick effect will be limited; if the porosity is greater than 30%, the first hard skeleton will be relatively loose, affecting the wear resistance and structural stability of the first hard skeleton.

[0005] According to an embodiment of the present invention, the non-stick filler is contained in any cross section of the first coating layer at a distance greater than or equal to X from the first surface, X is 20 to 100 micrometers, and X is less than the thickness of the first coating layer.

[0006] According to an embodiment of the present invention, any of the cross sections and / or longitudinal sections of the first coating contains the first hard skeleton and the non-stick filler.

[0007] According to an embodiment of the present invention, the distance between the first coating and the first surface is greater than or equal to 1 mm on any cross section of X. 2 The first hard skeleton and the non-stick filler are contained in the region at the same time.

[0008] According to an embodiment of the present invention, 1 mm of any cross section or longitudinal section of the first coating 2 The first hard skeleton and the non-stick filler are contained in the region.

[0009] According to an embodiment of the present invention, at 1 mm of any of the cross sections or longitudinal sections of the first coating, 2 In the region, the area ratio of the first hard skeleton to the non-stick filler is 2 to 19.

[0010] According to an embodiment of the present invention, the width of the pores is 5 to 150 micrometers.

[0011] According to an embodiment of the present invention, the particle size of the non-stick filler is smaller than or equal to the minimum value of the width of the pores.

[0012] According to an embodiment of the present invention, the first hard skeleton is formed by stacking particles, and the gaps between the particles constitute the pores.

[0013] According to an embodiment of the present invention, the thickness of the first coating layer is 50-300 micrometers.

[0014] According to an embodiment of the present invention, the non-stick coating and the substrate layer are combined by at least one of the following methods: a surface of the non-stick coating close to the substrate layer has a first concave-convex structure, a surface of the substrate layer close to the non-stick coating has a second concave-convex structure, and the non-stick coating and the substrate layer are combined by the first concave-convex structure and the second concave-convex structure interlocking with each other; the non-stick coating and the substrate layer are combined by a metallurgical method in which a portion of the material of the surface of the non-stick coating close to the substrate layer diffuses into the substrate layer.

[0015] According to an embodiment of the present invention, the non-stick coating further comprises a second coating, the second coating is disposed on a surface of the first coating close to the substrate layer, and the second coating comprises a second hard skeleton.

[0016] According to an embodiment of the present invention, the second hard skeleton and the first hard skeleton are an integrated structure. Optionally, the hardness of the first hard skeleton and / or the second hard skeleton is greater than or equal to 200 HV.

[0017] According to an embodiment of the present invention, the porosity of the first hard skeleton is greater than or equal to the porosity of the second hard skeleton.

[0018] According to an embodiment of the present invention, the non-stick filler extends from the first coating layer to the second coating layer.

[0019] According to an embodiment of the present invention, the porosity of the second hard skeleton gradually increases in a direction approaching the first hard skeleton, and the porosity of the surface of the second hard skeleton close to the first hard skeleton is less than or equal to the porosity of the first hard skeleton.

[0020] According to an embodiment of the present invention, the thickness of the second coating layer is 1 / 10 to 1 / 3 of the thickness of the non-stick coating layer.

[0021] According to an embodiment of the present invention, the thickness of the second coating layer is 20-100 micrometers.

[0022] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned composite non-stick layer. According to an embodiment of the present invention, the method for preparing the composite non-stick layer comprises: forming a non-stick coating on the first surface of the substrate layer, the step of forming the non-stick coating comprises the step of forming a first coating, the step of forming the first coating comprises: forming a first hard skeleton by thermal spraying hard particles, the first hard skeleton has through pores, and the porosity of the first hard skeleton is 5%-30%; filling the pores with non-stick fillers to obtain the first coating. Thus, the first hard skeleton formed by thermal spraying can provide better wear resistance for the non-stick coating, and the non-stick fillers filled in the pores can provide good non-stick properties for the non-stick coating, that is, the composite non-stick layer prepared by the above method has good wear resistance and non-stick properties at the same time; in addition, the first hard skeleton is prepared by thermal spraying, so that the first hard skeleton and the substrate layer have a strong bonding strength, improve the stability between the layer structures, and the preparation process is mature, which is convenient for industrial production. Among them, the porosity of the first hard skeleton is 5%-30%. In this way, the proportion of pores is appropriate, which can effectively meet the filling of non-stick fillers, so that the composite non-stick layer has good non-stick properties and good wear resistance at the same time; if the porosity is less than 5%, the proportion of the non-stick surface area of ​​the non-stick coating is too low, and the non-stick effect will be limited; if the porosity is greater than 30%, the first hard skeleton will be relatively loose, affecting the wear resistance and structural stability of the first hard skeleton.

[0023] According to an embodiment of the present invention, the step of forming the first hard skeleton includes: melting the hard particles to obtain semi-molten particles with melted surfaces and unmelted interiors; thermally spraying the semi-molten particles onto the first surface and stacking them to form the first hard skeleton.

[0024] According to an embodiment of the present invention, the method of filling the non-stick filler into the pores includes: coating the surface of the first hard skeleton away from the substrate layer with a non-stick filler emulsion; allowing the non-stick filler emulsion to penetrate into the pores by at least one of ultrasound, negative pressure and vortex; and curing the non-stick filler emulsion immersed in the pores to obtain the first coating.

[0025] According to an embodiment of the present invention, the non-stick filler is a silicon-based non-stick filler, and the curing temperature is 250-320°C; the non-stick filler is a fluorine-based non-stick filler, and the curing temperature is 350-420°C.

[0026] According to an embodiment of the present invention, the step of forming the non-stick coating further includes: before forming the first hard skeleton, forming a second hard skeleton on the first surface by the thermal spraying.

[0027] In another aspect of the present invention, the present invention provides a cookware. According to an embodiment of the present invention, the cookware includes the composite non-stick layer described above, wherein the base material layer in the composite non-stick layer constitutes the cookware body of the cookware, and the non-stick coating in the composite non-stick layer is located on one side of the cooking space of the cookware. As a result, the cookware has good wear resistance and non-stick properties, thereby improving the performance and service life of the cookware. Those skilled in the art can understand that the cookware has all the features and advantages of the composite non-stick layer described above, which will not be described in detail here.

[0028] In another aspect of the present invention, the present invention provides a cooking utensil. According to an embodiment of the present invention, the cooking utensil includes the pot described above. Thus, the pot of the cooking utensil has good wear resistance and non-stick properties, thereby improving the performance and service life of the cooking utensil. It can be understood by those skilled in the art that the cooking utensil has all the features and advantages of the composite non-stick layer described above, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0030] Figure 1 is a schematic structural diagram of a composite non-stick layer in one embodiment of the present invention;

[0031] Figure 2is a schematic structural diagram of a non-stick coating in another embodiment of the present invention;

[0032] Figure 3 is a scanning electron microscope image of a non-stick coating in another embodiment of the present invention;

[0033] Figure 4 is a schematic structural diagram of a composite non-stick layer in another embodiment of the present invention;

[0034] Figure 5 It is a schematic structural diagram of a composite non-stick layer in yet another embodiment of the present invention.

[0035] The reference numerals are as follows: substrate layer 10 , first surface 11 , non-stick coating 20 , first coating 21 , first hard skeleton 211 , non-stick filler 212 , pores 213 , first concavo-convex structure 201 , second concavo-convex structure 101 , second coating 22 . DETAILED DESCRIPTION

[0036] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0037] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0038] In one aspect of the present invention, the present invention provides a composite non-stick layer. According to an embodiment of the present invention, referring to Figure 1 , Figure 2 and Figure 3 The composite non-stick layer comprises: a substrate layer 10, the substrate layer 10 has a first surface 11; a non-stick coating 20, the non-stick coating 20 is arranged on the first surface 11, the non-stick coating 20 comprises a first coating 21, the first coating 21 comprises a first hard skeleton 211 and a non-stick filler 212, the first hard skeleton has through pores 213, and the non-stick filler 212 is filled in the pores 213 ( Figure 2The first hard skeleton 211 has a porosity of 5% to 30%. Thus, the first hard skeleton 211 in the first coating 21 can provide the non-stick coating 21 with better wear resistance, and the non-stick filler 212 filled in the pores 213 can provide the non-stick coating 21 with good non-stick properties, that is, the composite non-stick layer of the present invention has good wear resistance and non-stick properties at the same time; in addition, the permeability of the pores 213 ensures the connectivity of the distribution of the non-stick filler 212 in the first coating 21, so that the composite non-stick layer can be better guaranteed to have good non-stick properties during long-term use. Among them, the porosity of the first hard skeleton is 5%-30%. In this way, the proportion of pores is appropriate, which can effectively meet the filling of non-stick fillers, so that the composite non-stick layer has good non-stick properties and good wear resistance at the same time; if the porosity is less than 5%, the proportion of the non-stick surface area of ​​the non-stick coating is too low, and the non-stick effect will be limited; if the porosity is greater than 30%, the first hard skeleton will be relatively loose, affecting the wear resistance and structural stability of the first hard skeleton.

[0039] In some embodiments, the hardness of the first hard skeleton is greater than or equal to 200HV. In some specific embodiments, the hardness of the first hard skeleton can be higher than that of a stainless steel spatula (the hardness of stainless steel is less than or equal to 210HV). Thus, the hardness of the first hard skeleton is relatively high, providing good hardness and mechanical properties for the non-stick coating, ensuring that the non-stick coating will not be damaged by external forces during long-term use. Among them, the test method for the hardness of the first hard skeleton can be: using a Vickers hardness tester, taking three test points in the middle of the first hard skeleton or the first coating and taking the average of their hardness test values, which is the average value of the first hard skeleton.

[0040] According to an embodiment of the present invention, the thickness of the first coating 21 is 50 to 300 microns, such as 50 microns, 80 microns, 100 microns, 120 microns, 150 microns, 180 microns, 200 microns, 230 microns, 250 microns, 270 microns, and 300 microns, that is, the thickness of the first hard skeleton is 50 to 300 microns, so that good strength is provided for the composite non-stick layer. When the first coating 21 is directly attached to the substrate layer 10, the above thickness can make the first coating adhere well to the substrate layer, thereby improving the interlayer bonding force between the two. If the thickness of the composite non-stick coating is less than 50 μm, there is a risk of wear-through in long-term use, and the long-term use requirements of users cannot be fully met. If the composite non-stick coating exceeds 300 microns, it will not be of substantial help to the service life of the product. On the contrary, the excessive thickness of the composite non-stick coating will reduce the interface bonding strength between the composite non-stick coating and the substrate layer.

[0041] According to an embodiment of the present invention, a non-stick filler 212 is contained in any cross section of the first coating 21 at a distance greater than or equal to X from the first surface 11, X is 20 to 100 microns, and X is less than the thickness of the first coating, for example, X can be specifically 20 microns, 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns. Thus, any cross section of the first coating 21 of a certain thickness away from the substrate layer 10 contains both the first hard skeleton and the non-stick filler, which illustrates the connectivity of the pores, that is, the connectivity of the distribution of the non-stick filler 212. In this way, during long-term use, the first coating 21 will be worn to a certain extent, so that the thickness of the first coating 21 is gradually reduced, so the above requirements can well ensure that the non-stick property of the composite non-stick layer will not deteriorate or fail with the thinning of the thickness of the first coating 21 during long-term use, that is, the composite non-stick layer can well ensure the good wear resistance and non-stick property of the non-stick coating away from the substrate layer surface during long-term use. The cross section refers to the cross section of the composite non-stick layer in a direction perpendicular to the thickness direction of the composite non-stick layer, and the cross section of the composite non-stick layer in the thickness direction of the composite non-stick layer is the longitudinal cross section.

[0042] In some specific embodiments, the distance between the first coating 21 and the first surface 11 is greater than or equal to 1 mm on any cross section of X. 2 The first hard skeleton 211 and the non-stick filler 212 are contained in the region. Thus, in any cross section of the first coating 21 of a certain thickness away from the substrate layer 10, the 1 mm 2 The region contains both the first hard skeleton and the non-stick filler, which further fully illustrates the connectivity of the pores, that is, the connectivity of the distribution of the non-stick filler 212, and the distribution density of the non-stick filler is relatively large, which can better ensure the non-stickiness of the non-stick coating and the uniformity of the distribution of the non-stick performance. In this way, during long-term use, the first coating 21 will be worn to a certain extent, so that the thickness of the first coating 21 gradually decreases. Therefore, the above requirements can well ensure that the non-stickiness of the composite non-stick layer will not deteriorate or fail with the thinning of the thickness of the first coating 21 during long-term use, that is, the composite non-stick layer can well ensure that the non-stick coating is away from the surface of the substrate layer. Good wear resistance and non-stickiness. Among them, the cross section refers to the cross section of the composite non-stick layer in the direction perpendicular to the thickness direction of the composite non-stick layer, and the cross section of the composite non-stick layer in the thickness direction of the composite non-stick layer is a longitudinal section.

[0043] Further, as mentioned above, the thickness of the first coating 21 is 50 to 300 microns. If the thickness of the first coating 21 is relatively thin, such as 50 to 100 microns, then in the above requirement “any cross section of the first coating 21 at a distance greater than or equal to X (X is 20 to 100 microns) from the first surface 11 contains both the first hard skeleton and the non-stick filler”, a lower spacing may be selected for X, such as X being 20 to 30 microns or X being 20 to 50 microns, and “any cross section of the first coating 21 at a distance greater than or equal to 20 to 30 microns (or 20 to 50 microns) from the first surface 11 contains both the first hard skeleton and the non-stick filler”, that is, the spacing between any cross section in the above “any cross section contains both the first hard skeleton and the non-stick filler” and the first surface is 20 to 30 microns or 20 to 50 microns. In some specific embodiments, the thickness of the first coating 21 is 50 microns, and at the same time, any cross-section of the first coating 21 at a distance greater than or equal to 20 microns from the first surface 11 contains both the first hard skeleton and the non-stick filler; in other specific embodiments, the thickness of the first coating 21 is 70 microns, and at the same time, any cross-section of the first coating 21 at a distance greater than or equal to 30 microns from the first surface 11 contains both the first hard skeleton and the non-stick filler; in some other specific embodiments, the thickness of the first coating 21 is 100 microns, and at the same time, any cross-section of the first coating 21 at a distance greater than or equal to 50 microns from the first surface 11 contains both the first hard skeleton and the non-stick filler.

[0044] According to an embodiment of the present invention, any cross section or longitudinal section of the first coating contains the first hard skeleton and the non-stick filler. It can further ensure that the pores are connected from the upper surface to the lower surface of the first coating (that is, the first hard skeleton has a through pore 213, and the non-stick filler 212 is filled in the pore 213), which can effectively ensure the connectivity of the non-stick filler in the first coating. At the same time, it also further ensures the uniformity of the first hard skeleton. Therefore, on the one hand, it can ensure the good non-stickiness of the composite non-stick layer, and on the other hand, it can well ensure the good wear resistance of the composite non-stick layer. In some specific embodiments, 1mm in any cross section or longitudinal section of the first coating 2 The first hard skeleton and the non-stick filler are contained in the region. Thus, the permeability of the pores and the connectivity of the non-stick filler can be further ensured, and at the same time, the uniformity of the first hard skeleton can be further ensured. Therefore, on the one hand, the good non-stick property of the composite non-stick layer can be ensured, and on the other hand, the good wear resistance of the composite non-stick layer can be well ensured. Furthermore, in some embodiments, 1 mm in any cross section or longitudinal section of the first coating 2In the region of 1 mm2, the area ratio of the first hard skeleton to the non-stick filler is 2 to 19, for example, the area ratio of the first hard skeleton to the non-stick filler is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. 2 In the region of 1 mm in diameter, the area ratio of the first hard skeleton and the non-stick filler affects the non-stickiness and wear resistance of the composite non-stick layer. The above ratio range of 2 to 19 can well meet the requirements of the non-stickiness and wear resistance of the composite non-stick layer when it is used in cookware; when the first coating has a cross section or longitudinal section of 1 mm 2 In the region of 1 mm in diameter, when the area ratio of the first hard skeleton to the non-stick filler is less than 2, the area ratio of the first hard skeleton is too small, the wear resistance of the composite non-stick layer is relatively poor, and the composite non-stick layer is easily worn during cooking and cleaning; ... 2 In the region, when the area ratio of the first hard skeleton and the non-stick filler is greater than 19, the area of ​​the non-stick filler accounts for too small a proportion, the non-stickiness of the composite non-stick layer is relatively poor, and it is relatively difficult to clean.

[0045] It should be noted that in the product with the same composite non-stick layer, the composite non-stick layer has different 1mm in different cross sections or longitudinal sections. 2 In the region, the area ratio of the first hard skeleton and the non-stick filler can be the same or different. If different, it only needs to be between 2 and 19.

[0046] According to an embodiment of the present invention, the porosity difference at any cross section or longitudinal section of the first hard skeleton is less than or equal to 2.0%. For example, the porosity difference at any cross section or longitudinal section of the first hard skeleton is 2.0%, 1.8%, 1.6%, 1.4%, 1.2%, 1.0%, 0.8%, 0.6%, 0.5%, 0.4%, 0.2%, 0.1%, 0.05% or 0. In this way, at different positions, the porosity of the first coating does not change much, that is, the porosity has good stability, which makes the wear resistance and non-stickiness of the first coating uniform, avoiding poor local non-stickiness or poor wear resistance; moreover, with long-term use, even if the first coating is worn to a certain thickness, it will still maintain good non-stickiness and wear resistance. Meet the use requirements of the cookware. It should be noted that, in the product of the same composite non-stick layer, the porosity difference between any two cross-sections or longitudinal sections of the first hard skeleton may be equal or not completely equal, as long as it is less than or equal to 2.0%. In this way, the uniformity of the wear resistance and non-stick properties of the first coating can be guaranteed.

[0047] According to an embodiment of the present invention, the width of the pore is 5 to 150 microns. For example, the width of the pore is 5 microns, 10 microns, 20 microns, 40 microns, 50 microns, 80 microns, 100 microns, 110 microns, 120 microns, 130 microns, 140 microns, and 150 microns, which can effectively ensure that the non-stick filler is smoothly filled into the pore and at the same time ensure the good hardness of the hard skeleton; if the width of the pore is less than 5 μm, not only will the narrow penetration channel of the emulsion of the non-stick filler affect the filling effect, but the emulsion of the non-stick filler will also need to overcome the additional pressure caused by surface tension when penetrating into the interior of the pore, affecting the penetration effect; if the width of the pore is greater than 150 μm, the porous first hard skeleton is relatively loose. Although the emulsion penetration of the non-stick filler becomes easier, the overall structural strength of the porous first hard skeleton decreases, and the porous first hard skeleton is easily destroyed. It should be noted that in the same composite non-stick layer product, the widths of the pores at different positions may vary, as long as the width of the pores is between 5 μm and 150 μm.

[0048] According to an embodiment of the present invention, the first hard skeleton is formed by stacking particles, and the gaps between the particles constitute pores. In this way, the particles have a better bonding force, so that the first hard skeleton has good stability. At the same time, the way the particles are stacked makes the gaps between the particles form pores with through gaps, thereby further improving the connectivity of the pores. In some embodiments, the particle size of the particles is 50 microns to 100 microns, so that it can help to obtain the above-mentioned first hard skeleton with a width of 5 to 150 microns, pores, and a porosity of 5%-30%. If the particle size of the particles is too small, the gaps between the particles are small during the particle stacking process, thereby reducing the porosity of the first hard skeleton and even affecting the connectivity of the pores; if the particle stacking is large, the gaps between the particles will be larger, which will greatly improve the porosity of the first hard skeleton, resulting in an overall larger porosity of the first hard skeleton, affecting the wear resistance of the first coating. The first hard skeleton is prepared by hard particles. During the preparation process, the hard particles are gradually sprayed on the substrate in a semi-molten state to form the first hard skeleton in the form of particles stacked on each other (ie, particle stacking).

[0049] According to an embodiment of the present invention, the non-stick coating layer and the substrate layer may be combined by interlocking or / and metallurgical bonding, as follows:

[0050] In some embodiments, reference Figure 4The surface of the non-stick coating 20 close to the substrate layer 10 has a first concavo-convex structure 201, and the surface of the substrate layer 10 close to the non-stick coating 20 has a second concavo-convex structure 101. The non-stick coating 20 and the substrate layer 10 are combined by the first concavo-convex structure 201 and the second concavo-convex structure 101 interlocking with each other. In this way, the non-stick coating and the substrate layer are embedded in each other, which greatly improves the bonding force between the non-stick coating and the substrate layer, thereby improving the structural stability of the composite non-stick layer. In the process of preparation, the hard particles are sprayed on the surface of the substrate layer, so that the hard particles are partially embedded in the substrate layer, thereby generating the second concavo-convex structure 101 on the surface of the substrate layer close to the non-stick coating. Since the first hard skeleton is formed by stacking particles, that is, the surface of the non-stick coating close to the substrate layer is also formed by hard particles, so that the surface of the non-stick coating close to the substrate layer forms the first concavo-convex structure 201. Due to the above reasons, the first concavo-convex structure and the second concavo-convex structure formed can be closely interlocked with each other, thereby effectively improving the bonding force between the non-stick coating and the substrate layer.

[0051] In other embodiments, the non-stick coating 20 and the substrate layer 10 are combined by metallurgical means in which a portion of the material of the surface of the non-stick coating 20 close to the substrate layer 10 diffuses into the substrate layer 10, that is, when preparing the non-stick coating, a portion of the material used to prepare the first hard skeleton diffuses into the substrate layer, so that the material of the first hard skeleton in the substrate layer is connected to the first hard skeleton as a whole, effectively improving the bonding force between the non-stick coating 20 and the substrate layer 10, thereby improving the structural stability of the composite non-stick layer. In still other embodiments, the bonding between the non-stick coating 20 and the substrate layer 10 has both mutual bite bonding and metallurgical bonding, which greatly improves the bonding force between the non-stick coating and the substrate layer, thereby improving the structural stability of the composite non-stick layer.

[0052] According to an embodiment of the present invention, referring to Figure 5 The non-stick coating 20 further includes a second coating 22, which is disposed on the surface of the first coating 21 close to the substrate layer 10, and includes a second hard skeleton. Thus, the second coating 22, as a transition layer, can further improve the bonding strength between the non-stick coating 20 and the substrate layer 10, thereby further improving the overall structural stability of the composite non-stick layer and extending the service life of the cookware using the composite non-stick layer.

[0053] In some embodiments, the hardness of the first hard skeleton is greater than or equal to 200 HV. In some specific embodiments, the hardness of the first hard skeleton can be higher than that of a stainless steel spatula (the hardness of stainless steel is less than or equal to 210 HV). Thus, the hardness of the first hard skeleton is relatively high, providing good hardness and mechanical properties for the non-stick coating, ensuring that the non-stick coating will not be damaged by external forces during long-term use. The test method for the hardness of the second hard skeleton is the same as the test method for the hardness of the first hard skeleton.

[0054] Those skilled in the art can understand that if the non-stick coating 20 only includes the first coating 21, the first coating 21 is directly disposed in contact with the substrate layer 10, and the first coating 21 and the substrate layer 10 can be combined by mutual interlocking or / and metallurgical bonding; if the non-stick coating 20 includes the first coating 21 and the second coating 22, the second coating 22 is directly disposed in contact with the substrate layer 10, and the second coating 22 and the substrate layer 10 can be combined by mutual interlocking or / and metallurgical bonding.

[0055] According to an embodiment of the present invention, the second hard skeleton and the first hard skeleton are an integrated structure. Thus, the integrity of the non-stick coating can be better ensured, thereby improving the structural stability of the non-stick coating. In some embodiments, the first hard skeleton and the second hard skeleton can be prepared by the same method, such as both are prepared by thermal spraying, so that the first hard skeleton and the second hard skeleton can be prepared by the same process, and during preparation, only certain process parameters need to be adjusted, so that the connectivity between the first hard skeleton and the second hard skeleton is stronger, which can further improve the bonding strength between the two and the bonding strength between the non-stick coating and the substrate layer.

[0056] According to an embodiment of the present invention, the second coating 22 serves as a transition layer, and the second hard skeleton has a porous structure with a porosity of 1% to 20%, and the porosity of the first hard skeleton is greater than or equal to the porosity of the second hard skeleton. Specifically, the porosity of the second hard skeleton can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. As a result, the structure of the second hard skeleton in the second coating 22 is denser than the structure of the first hard skeleton 211 in the first coating 21, so that the second coating 22 can be firmly combined with the substrate layer 10, which is conducive to improving the bonding strength between the non-stick coating 20 and the substrate layer 10, and further helps to extend the service life of the cookware; in addition, the structure of the transition layer is relatively dense, even if the non-stick material filled in the pores of the hard skeleton is destroyed, the corrosive medium is not easy to penetrate into the substrate, so that the corrosion resistance of the cookware can be further improved.

[0057] According to an embodiment of the present invention, in the direction close to the first hard skeleton 211, the porosity of the second hard skeleton gradually increases, and the porosity of the surface of the second hard skeleton close to the first hard skeleton 211 is less than or equal to the porosity of the first hard skeleton 211. As a result, the structure of the side of the second hard skeleton close to the substrate layer is more compact, which can further improve the bonding strength between the non-stick coating and the substrate layer, and can also further improve the corrosion resistance of the composite non-stick layer. In some specific embodiments, in the direction close to the first hard skeleton 211, the porosity of the second hard skeleton gradually increases from 1% to the porosity of the first hard skeleton or close to the porosity of the first hard skeleton.

[0058] Furthermore, the non-stick filler extends from the first coating to the second coating, that is, the pores of the second hard skeleton can also be further filled with non-stick fillers, that is, when the non-stick fillers are filled into the pores in the first hard skeleton, part of the non-stick fillers penetrate from the pores of the first hard skeleton into the pores of the second hard skeleton, which can play a role of "anchoring" and fixed connection, further increasing the bonding force between the first coating and the second coating, and does not affect its non-stick performance. Among them, the non-stick filler can fill the pores of the second hard skeleton completely or partially, and those skilled in the art can flexibly choose according to actual needs, and no restriction is made here.

[0059] According to an embodiment of the present invention, the thickness of the second coating is 1 / 10 to 1 / 3 of the thickness of the non-stick coating (the sum of the thickness of the first coating and the second coating). For example, the thickness of the second coating is 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, 1 / 3, etc. Therefore, the thickness ratio of the second coating can not only play a transitional role and further improve the bonding strength between the non-stick coating 20 and the substrate layer 10, but also ensure that the thickness ratio of the first coating is relatively large, so that during the long-term use of the composite non-stick layer, the first coating will not be completely worn through, affecting the non-stick property of the composite non-stick layer.

[0060] In some embodiments of the present invention, the thickness of the second coating layer is 20 to 100 microns, for example, the thickness of the second coating layer is 20 microns, 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns or 100 microns. The thickness of the second coating layer can play a good transition role and further improve the bonding strength between the non-stick coating layer 20 and the substrate layer 10.

[0061] In the embodiment of the present invention, the material of the substrate layer includes but is not limited to stainless steel, aluminum alloy, iron, titanium alloy and the like. Thus, the substrate layer has good thermal conductivity and strength, meeting the use requirements of the cookware.

[0062] In an embodiment of the present invention, the hard skeleton is a metal-based skeleton, a ceramic-based skeleton or a metal / ceramic-based skeleton. The hard skeleton of the above material has good wear resistance and thermal conductivity, and meets the use requirements of the cookware. Furthermore, the metal-based skeleton is at least one of a mixed material of stainless steel and a boron-containing iron-based material, a titanium-based alloy and an iron-based amorphous system material. In some embodiments, the metal-based skeleton includes iron and auxiliary raw materials, and the auxiliary raw materials include at least one of chromium Cr, boron B, silicon Si, carbon C, nickel Ni and oxygen O. Therefore, Fe is selected as the main element. The cost of Fe is low, and the thermal conductivity layer and wear resistance are good, which can well meet the use requirements of cookware. In addition, Fe has been used to make cookware since ancient times and has good user acceptance. Adding Cr and Ni can help improve the corrosion resistance of the composite non-stick coating to solve the problem that iron pans are prone to rust. C, B, and Si are the elements that form iron-based amorphous materials. Amorphous materials have no grain boundaries, which can avoid grain boundary corrosion and further improve corrosion resistance. At the same time, amorphous materials have higher hardness. O can form a Cr2O3 protective film with Cr, which is also beneficial to improving the corrosion resistance of the composite non-stick coating.

[0063] According to an embodiment of the present invention, the non-stick filler is an organic non-stick material or an inorganic non-stick material containing fluorine or silicon, such as PTFE, PFA, fluorosilane, siloxane and other non-stick materials. Therefore, the non-stick filler is a low surface energy infiltrate, a nanometer or ultra-fine micrometer-level super-hydrophobic medium, and the non-stick filler can ensure unimpeded passage through the smallest pore size in the hard skeleton. In some embodiments, the particle size of the non-stick filler is less than or equal to the minimum value of the width of the pore, so that it can better ensure that the non-stick filler can be more smoothly immersed in the pores of the first hard skeleton.

[0064] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned composite non-stick layer. According to an embodiment of the present invention, the method for preparing the composite non-stick layer comprises: forming a non-stick coating 20 on the first surface 11 of the substrate layer 10, the step of forming the non-stick coating 20 comprises the step of forming a first coating 21, and the step of forming the first coating 21 comprises:

[0065] S100: forming a first hard skeleton 211 by thermal spraying, wherein the first hard skeleton 211 has through pores 213 , and the porosity of the first hard skeleton 211 is 5%-30%.

[0066] In an embodiment of the present invention, the process conditions of thermal spraying meet at least one of the following: the particle size of the hard particles is 5 to 100 microns (for example, 5 microns, 10 microns, 20 microns, 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns); the powder feeding rate is 0.5 to 3 r / min (for example, 0.5 r / min, 1.0 r / min, 1.5 r / min, 2.0 r / min, 2.5 r / min, 3.0 r / min); the acetylene flow rate is 3 to 10 L / min (for example, 3 L / min, 4 L / min, 5 L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min); oxygen flow rate is 3-10L / min (for example, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min); spraying distance is 20-150mm (for example, 20mm, 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm). Thus, under the above-mentioned thermal spraying process conditions, a first hard skeleton with suitable pore width, suitable thickness and better porosity can be effectively obtained, so that the parameters such as pore width, thickness and porosity of the first hard skeleton meet the range requirements described above.

[0067] In an embodiment of the present invention, the step of forming the first hard skeleton includes: melting the hard particles to obtain semi-molten particles with melted surfaces and unmelted interiors; then thermally spraying the semi-molten particles on the first surface to stack and form the first hard skeleton. In the above process, the hard particles are melted into semi-molten particles before thermal spraying, and the molten surfaces of two adjacent hard particles can be fused together, which can greatly improve the bonding strength between the particles, thereby improving the structural stability of the first hard skeleton.

[0068] Furthermore, the thickness of the semi-molten particles that are melted can be 1 / 10 to 1 / 3 of the particle size of the hard particles, for example, the thickness of the semi-molten particles that are melted can be 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, 1 / 3, etc. of the particle size of the hard particles. In this way, the molten surfaces of two adjacent hard particles can be well fused together, greatly improving the bonding strength between the particles, while the melted parts of the semi-molten particles will not fill the gaps between the particles, affecting the width and connectivity of the pores.

[0069] S200: Fill the pores 213 with non-stick filler 212 to obtain a first coating 21. The structural diagram can be found in Figure 2 and Figure 3 .

[0070] In an embodiment of the present invention, the method of filling the pores 213 with the non-stick filler 212 includes:

[0071] S210: coating the non-stick filler emulsion on the surface of the first hard skeleton 211 away from the substrate layer 10. There is no special requirement for the specific coating method, and those skilled in the art can flexibly select it according to actual conditions.

[0072] The non-stick filler is an organic non-stick material or an inorganic non-stick material containing fluorine or silicon, such as PTFE, PFA, fluorosilane, siloxane, etc. Therefore, the non-stick filler is a low surface energy impregnant, a nanometer or ultra-fine micrometer-level super-hydrophobic medium, and the non-stick filler can ensure unimpeded passage through the smallest pore size in the hard skeleton.

[0073] S220: The non-stick filler emulsion is immersed into the pores by at least one of ultrasound, negative pressure and vortex. In this way, the above method is simple and easy to implement, and can effectively immerse the non-stick filler emulsion into the pores, thereby improving the utilization rate of the non-stick filler.

[0074] In some embodiments, the specific method of making the non-stick filler emulsion penetrate into the pores by ultrasound can be: coating the surface of the first hard skeleton with the non-stick filler emulsion, and then placing it in an ultrasonic environment for ultrasound. The ultrasonic process conditions are: frequency ≥ 20KHz, power density ≥ 0.3W / cm 2 , the ultrasonic temperature is 20-40℃, and the ultrasonic time is 5-30min. Under the above conditions, the non-stick filler emulsion can quickly and evenly penetrate into the pores to fill the pores of the first hard skeleton; and the above conditions are relatively mild, and the bonding force between the first hard skeleton and the substrate layer will not be affected by ultrasound.

[0075] In some embodiments, the specific method of allowing the non-stick filler emulsion to penetrate into the pores by negative pressure can be: coating the surface of the first hard skeleton with the non-stick filler emulsion, and then placing it in a negative pressure environment. The process conditions of the negative pressure are: during the process of the non-stick filler emulsion penetrating into the pores, the negative pressure is 0.15 to 0.4 bar at room temperature, and the negative pressure infiltration time is 5 to 30 minutes. Therefore, under the above conditions, the non-stick filler emulsion can be quickly and evenly penetrated into the pores to fill the pores of the first hard skeleton; moreover, the effect of the negative pressure will not have an adverse effect on the bonding force between the first hard skeleton and the substrate layer.

[0076] In some embodiments, the specific method of immersing the non-stick filler emulsion into the pores by vortexing can be: placing the first hard skeleton into the non-stick filler emulsion, and stirring the non-stick filler emulsion at a certain stirring rate. Among them, the process conditions of the vortex are: at room temperature, the stirring speed is 100-500rpm, the stirring time is 5-30min, and the stirring amount is 20-100ml / piece (that is, the stirring amount is the volume that each stirring bar is responsible for stirring, and the number of stirring bars put in can be confirmed based on the total amount of non-stick filler emulsion). Thus, under the above conditions, the non-stick filler emulsion can be quickly and evenly immersed in the pores to fill the pores of the first hard skeleton; moreover, the effect of the vortex will not have an adverse effect on the bonding force between the first hard skeleton and the substrate layer.

[0077] S230 : curing the non-stick filler emulsion impregnated into the pores to obtain a first coating layer 21 .

[0078] In some embodiments, the non-stick filler is a silicon-based non-stick filler, and the curing temperature is 250-320° C., such as 250° C., 260° C., 270° C., 280° C., 290° C., 300° C., 310° C., 320° C. Thus, at the above temperature, the non-stick filler emulsion can be quickly cured without causing adverse effects on the first hard skeleton and the non-stick filler.

[0079] In some embodiments, the non-stick filler is a fluorine-based non-stick filler, and the curing temperature is 350-420° C., such as 350° C., 360° C., 370° C., 380° C., 390° C., 400° C., 410° C., 420° C. Thus, at the above temperature, the non-stick filler emulsion can be quickly cured without causing adverse effects on the first hard skeleton and the non-stick filler.

[0080] In an embodiment of the present invention, after the non-stick filler is cured, the surface of the first coating is sandblasted or polished to remove the surface heterogeneous layer, and finally a non-stick coating with a porous framework and low surface energy substances in the pores interlocked is obtained.

[0081] According to the embodiment of the present invention, the first hard skeleton formed by thermal spraying can provide better wear resistance for the non-stick coating, and the non-stick filler filled in the pores can provide good non-stick properties for the non-stick coating, that is, the composite non-stick layer prepared by the above method has good wear resistance and non-stick properties at the same time; in addition, by preparing the first hard skeleton by thermal spraying, the first hard skeleton and the substrate layer can have a strong bonding strength, improve the stability between the layer structures, and the preparation process is mature and convenient for industrial production. Among them, the porosity of the first hard skeleton is 5%-30%, so that the proportion of pores is appropriate, which can effectively meet the filling of non-stick fillers, so that the composite non-stick layer has good non-stick properties and good wear resistance at the same time; if the porosity is less than 5%, then the proportion of the non-stick surface area of ​​the non-stick coating is too low, and the non-stick effect will be limited; if the porosity is greater than 30%, then the first hard skeleton will be relatively loose, affecting the wear resistance and structural stability of the first hard skeleton.

[0082] According to an embodiment of the present invention, the step of forming the non-stick coating 20 further includes: before forming the first hard skeleton 211, forming a second hard skeleton on the first surface 11 by thermal spraying for forming the second coating 22, such as Figure 5 The second hard skeleton as a transition layer can further improve the bonding strength between the non-stick coating 20 and the substrate layer 10, thereby further improving the overall structural stability of the composite non-stick layer and extending the service life of the cookware using the composite non-stick layer.

[0083] According to an embodiment of the present invention, the second hard skeleton and the first hard skeleton are an integrated structure, and both the first hard skeleton and the second hard skeleton are prepared by thermal spraying. In this way, the first hard skeleton and the second hard skeleton can be prepared by one process, and during the preparation, only certain process parameters need to be adjusted.

[0084] According to the embodiment of the present invention, the porosity of the second hard skeleton gradually increases in the direction close to the first hard skeleton 211, and the porosity of the surface of the second hard skeleton close to the first hard skeleton 211 is less than or equal to the porosity of the first hard skeleton 211. Therefore, the structure of the side of the second hard skeleton close to the substrate layer is more compact, which can further improve the bonding strength between the non-stick coating and the substrate layer, and can also further improve the corrosion resistance of the composite non-stick layer.

[0085] Furthermore, the pores of the second hard skeleton can be further filled with non-stick fillers, that is, when the non-stick fillers are filled into the pores in the first hard skeleton, part of the non-stick fillers penetrate from the pores of the first hard skeleton into the pores of the second hard skeleton, wherein the non-stick fillers can fill the pores of the second hard skeleton fully or partially. The technical personnel in this field can flexibly choose according to actual needs, and no restrictions are imposed here.

[0086] In another aspect of the present invention, the present invention provides a cookware. According to an embodiment of the present invention, the cookware includes the composite non-stick layer described above, wherein the base material layer in the composite non-stick layer constitutes the cookware body of the cookware, and the non-stick coating in the composite non-stick layer is located on one side of the cooking space of the cookware. As a result, the cookware has good wear resistance and non-stick properties, thereby improving the performance and service life of the cookware. Those skilled in the art can understand that the cookware has all the features and advantages of the composite non-stick layer described above, which will not be described in detail here.

[0087] In another aspect of the present invention, the present invention provides a cooking utensil. According to an embodiment of the present invention, the cooking utensil includes the pot described above. Thus, the pot of the cooking utensil has good wear resistance and non-stick properties, thereby improving the performance and service life of the cooking utensil. It can be understood by those skilled in the art that the cooking utensil has all the features and advantages of the composite non-stick layer described above, which will not be described in detail here.

[0088] In the embodiments of the present invention, there is no special requirement for the specific type of the above-mentioned cooking utensils, and those skilled in the art can flexibly select according to actual conditions. In some embodiments, the above-mentioned cooking utensils can be a frying pan, a stew pot, an electric rice cooker, a pressure cooker, a milk pan, a frying pan, a steamer, etc.

[0089] Example

[0090] Examples 1 to 15 and comparative examples 1 to 2 are shown in Table 1, wherein the steps of preparing the composite non-stick layer include:

[0091] A first hard skeleton is formed on the first surface of the substrate layer by thermal spraying, wherein the material forming the first hard skeleton is a mixed material of stainless steel 304 and boron-containing iron-based, wherein the mass content of boron is 3%;

[0092] Applying a silicone-based non-stick filler emulsion to a surface of the first hard skeleton away from the substrate layer;

[0093] The non-stick filler emulsion is infiltrated into the pores by ultrasound;

[0094] The non-stick filler emulsion impregnated into the pores is cured at 300° C. to obtain a first coating;

[0095] The surface of the first coating is sandblasted and polished to remove the surface heterogeneous layer to obtain a non-stick coating.

[0096] Example 16

[0097] The difference between the preparation of the composite non-stick layer in Example 16 and the above Examples 1 to 15 is that the material forming the first hard skeleton is 430 stainless steel.

[0098] The parameters and test results of the porosity, pore size and thickness of the non-stick coating (which is the same as the thickness of the first coating in this embodiment) of the first hard skeleton in the above-mentioned embodiments 1 to 16 and comparative examples 1 to 2 can be found in Table 1 below. The test method is as follows:

[0099] 1. Salt spray test: According to GB / T 10125 "Artificial atmosphere corrosion test salt spray test", place the finished product samples in a neutral salt spray test box at 35℃±2℃, spray continuously with 5% sodium chloride solution, take out every 12 hours, rinse with water and air dry, and visually inspect the surface quality.

[0100] 2. Hardness test: Use a microhardness tester to test the hardness of the coating. Randomly select five locations on the sample surface for testing, use a 0.2 kgf load and a diamond square cone with a vertex angle of 136° to press into the material surface and hold the pressure for 30 seconds, and divide the load value by the surface area of ​​the material indentation pit to obtain the Vickers hardness value.

[0101] 3. Wear test: Fix the sample on the plane wear tester, with the porous skeleton layer of the sample facing up and a scouring pad placed flat, apply a load of 2.5kg on the scouring pad, set the frequency to 33 times / min, apply push and pull force, one back and forth movement is one cycle, and the unidirectional movement distance is 10cm. Start the plane wear tester, replace the friction surface of the scouring pad every 500 times, and observe the surface state of the coating.

[0102] 4. Non-stick test: Use SINDIN SDC-350 contact angle meter to test the hydrophobic angle of the initial wear-resistant non-stick layer surface and the surface after 100,000 times of wear by the flat wear tester, and observe the contact angle between the water droplet and the sample surface. The larger the hydrophobic angle, the better the non-stick property.

[0103] 5. Porosity test: Tested according to the national standard GB / T 17721-1999; or, in the embodiment of the present invention, 1 mm2 of any cross section or longitudinal section of the first coating. 2 The porosity is calculated in the region, and the calculation formula is: S 凹 / (S 凸 +S 凹 ), S 凸 It is expressed as the area value corresponding to the protruding part, S 凹 It is expressed as the area value corresponding to the concave part. The convex part is the hard skeleton, and the concave part is the pore where the non-stick filler penetrates. Therefore, the porosity is related to S 凸 and S 凹 Value related.

[0104] Table 1

[0105]

[0106]

[0107]

[0108] From the test results of Comparative Example 1, it can be seen that the porosity of the first hard skeleton is too small (<5%, measured 3%), so the proportion of low surface energy wettable substances is low, which cannot significantly improve the surface non-stickiness, and the hydrophobic angle value is low; Comparative Example 2 shows that when the skeleton porosity is too high (>30%, measured 50%), the skeleton will be relatively loose. Even if the intrinsic hardness of the skeleton material is very high, when the hardness test is performed, the indenter will collapse the loose skeleton on the surface, that is, the support of the skeleton is insufficient, resulting in a low actual hardness value. After 100,000 times of flat plate wear, the local position of the hard skeleton layer has been worn through, which is reflected in a significant decrease in the non-stickiness of the sample. In contrast, in Comparative Example 1, due to the low porosity, the measured value of the skeleton hardness is relatively high (550HV). In addition, the porosity is too high, and the porous first hard skeleton structure is unstable. Although the initial surface of the non-stick coating before wear has a high porosity and a high proportion of low surface energy infiltrates, which is manifested as a high initial hydrophobic angle value (135°), the protective effect of the loose skeleton on low surface energy infiltrates is limited. After the flat plate wear test, the skeleton is significantly damaged and the non-stickiness is greatly reduced. Example 7 shows that when the pore size is too small (<5 microns), the emulsion penetration channel is too narrow, which will affect the penetration effect. The further into the non-stick coating, the worse the emulsion penetration effect. After the flat plate is worn 100,000 times, since it has been worn to the inside of the non-stick coating, the low surface energy emulsion at this position does not form a good filling in the pores here, and the surface is not The viscosity will be lower; Example 10 shows that when the pore size is too large (>160 microns), the porous skeleton will be relatively loose, the overall structural strength of the porous skeleton will be reduced, the support and protection effect of the skeleton on the super-hydrophobic infiltrate will be reduced, and the wear-resistant non-stick layer is not worn through after 100,000 flat plate wears, but due to the damage of the skeleton, a certain proportion of the low surface energy infiltrate in the pores is destroyed, and the surface non-stickiness decreases to a certain extent; Example 11 shows that when the non-stick coating is too thin (<50 microns, 30 microns measured), the long-lasting protection of the porous first hard skeleton is insufficient. After 100,000 flat plate wears, the wear-resistant non-stick layer is worn through, and the non-stickiness is greatly reduced; Example 16 shows that the material of the first hard skeleton should be selected from corrosion-resistant metal or ceramic materials, otherwise it cannot pass the corrosion resistance test, and the non-stick coating is at risk of corrosion and rust in actual use.

[0109] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0111] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite non-stick layer, characterized in that: include: A substrate layer having a first surface; A non-stick coating, wherein the non-stick coating is arranged on the first surface, the non-stick coating comprises a first coating, the first coating comprises a first hard skeleton and a non-stick filler, the first hard skeleton has through pores, and the non-stick filler is filled in the pores, wherein the porosity of the first hard skeleton is 5%-30%.

2. The composite non-stick layer according to claim 1, characterized in that: The non-stick filler is contained in any cross section of the first coating layer at a distance greater than or equal to X from the first surface, X is 20 to 100 micrometers, and X is less than or equal to the thickness of the first coating layer.

3. The composite non-stick layer according to claim 2, characterized in that: Any of the cross sections and / or longitudinal sections of the first coating contains the first hard skeleton and the non-stick filler.

4. The composite non-stick layer according to claim 2, characterized in that: 1 mm on any cross section where the distance between the first coating and the first surface is greater than or equal to X 2 The first hard skeleton and the non-stick filler are contained in the region.

5. The composite non-stick layer according to claim 3, characterized in that: 1 mm of any of the cross sections and / or longitudinal sections of the first coating 2 The first hard skeleton and the non-stick filler are contained in the region.

6. The composite non-stick layer according to claim 5, characterized in that: 1 mm of any of the cross-sections and / or longitudinal sections of the first coating 2 In the region, the area ratio of the first hard skeleton to the non-stick filler is 2 to 19.

7. The composite non-stick layer according to claim 1, characterized in that: The width of the pores is 5 to 150 microns.

8. The composite non-stick layer according to claim 7, characterized in that: The particle size of the non-stick filler is less than or equal to the minimum value of the width of the pores.

9. The composite non-stick layer according to claim 1, characterized in that: The first hard skeleton is formed by stacking particles, and the gaps between the particles constitute the pores.

10. The composite non-stick layer according to any one of claims 1 to 9, characterized in that: The thickness of the first coating layer is 50 to 300 microns.

11. The composite non-stick layer according to any one of claims 1 to 9, characterized in that: The non-stick coating and the substrate layer are combined by at least one of the following methods: The surface of the non-stick coating layer close to the substrate layer has a first concavo-convex structure, and the surface of the substrate layer close to the non-stick coating layer has a second concavo-convex structure, and the non-stick coating layer and the substrate layer are combined in a manner that the first concavo-convex structure and the second concavo-convex structure are mutually engaged; The non-stick coating and the substrate layer are metallurgically bonded together by diffusion of a surface portion of the non-stick coating close to the substrate layer into the substrate layer.

12. The composite non-stick layer according to any one of claims 1 to 9, characterized in that: The non-stick coating further comprises a second coating, which is disposed on a surface of the first coating close to the substrate layer, and comprises a second hard skeleton.

13. The composite non-stick layer according to claim 12, characterized in that: The second rigid skeleton and the first rigid skeleton are an integral structure.

14. The composite non-stick layer according to claim 12, characterized in that: The porosity of the first hard skeleton is greater than or equal to the porosity of the second hard skeleton, and / or the hardness of the first hard skeleton and the second hard skeleton is greater than or equal to 200 HV.

15. The composite non-stick layer according to claim 14, characterized in that: The non-stick filler extends from the first coating layer to the second coating layer.

16. The composite non-stick layer according to claim 14, characterized in that: In the direction approaching the first hard skeleton, the porosity of the second hard skeleton gradually increases, and the porosity of the second hard skeleton near the surface of the first hard skeleton is less than or equal to the porosity of the first hard skeleton.

17. The composite non-stick layer according to claim 12, characterized in that: The ratio of the thickness of the second coating layer to the thickness of the non-stick coating layer is in the range of 1 / 10 to 1 / 3.

18. The composite non-stick layer according to claim 17, characterized in that: The thickness of the second coating layer is 20 to 100 micrometers.

19. A method for preparing the composite non-stick layer according to any one of claims 1 to 18, characterized in that: include: A non-stick coating is formed on the first surface of the substrate layer, wherein the step of forming the non-stick coating includes the step of forming a first coating, and the step of forming the first coating includes: Forming a first hard skeleton by thermal spraying hard particles, wherein the first hard skeleton has through pores and the porosity of the first hard skeleton is 5%-30%; The pores are filled with non-stick fillers to obtain the first coating layer.

20. The method according to claim 19, characterized in that The steps of forming the first hard skeleton include: The hard particles are melted to obtain semi-molten particles with melted surfaces and unmelted interiors; The semi-molten particles are thermally sprayed onto the first surface and stacked to form the first hard skeleton.

21. The method according to claim 19, characterized in that The method of filling the pores with the non-stick filler comprises: Applying a non-stick filler emulsion to the surface of the first hard skeleton away from the substrate layer; The non-stick filler emulsion is immersed into the pores by at least one of ultrasound, negative pressure and vortex; The non-stick filler emulsion impregnated into the pores is cured to obtain the first coating layer.

22. The method according to claim 21, characterized in that The non-stick filler is a silicon-based non-stick filler, and the curing temperature is 250-320°C; the non-stick filler is a fluorine-based non-stick filler, and the curing temperature is 350-420°C.

23. The method according to claim 19, characterized in that The step of forming the non-stick coating further comprises: Before forming the first hard skeleton, a second hard skeleton is formed on the first surface by the thermal spraying.

24. A cookware, characterized in that: It comprises the composite non-stick layer according to any one of claims 1 to 18, wherein the base material layer in the composite non-stick layer constitutes the cookware body of the cookware, and the non-stick coating in the composite non-stick layer is located on one side of the cooking space of the cookware.

25. A cooking utensil, characterized in that: The invention comprises the cookware as claimed in claim 24.

Citation Information

Patent Citations

  • Non-stick coating, cooker, preparation method of cooker and cooking appliance

    CN110840219A

  • Quasicrystal coating, preparation method thereof, and cooking utensil

    CN111202435A

  • Non-stick utensil

    CN112137418A

  • Composite non-stick coating and preparation method thereof, pot and cooking appliance

    CN112337773A

  • Composite coating, preparation method thereof, cookware and cooking utensil

    CN112773202A